Interfaith Ecotheology in Responding to the Global Ecological Crisis: Theological and Environmental Ethical Perspectives - Indra Irawan Sayuti, Sadip; Anwar, Khoerul; Ansori (Universitas Islam Negeri Raden Intan Lampung, 2026)
The global ecological crisis, characterized by environmental degradation, depletion of natural resources, and climate change, is not only caused by technical factors but is also rooted in a human ethical and spiritual crisis that has given rise to an anthropocentric and exploitative view of nature. This article aims to analyze the role of eco-theology based on the concept of divine stewardship in fostering interfaith collaboration as a response to the environmental crisis. This study employs a qualitative approach using literature review and comparative analysis of various religious traditions, namely Islam, Christianity, Judaism, Hinduism, and Buddhism. The research findings indicate that all religious traditions possess concepts of ecological responsibility rooted in the relationship between God, humanity, and nature. Common conceptual structures were identified, including a theocentric orientation, ethical-practical dimensions, and the principle of interconnectedness among all beings. Furthermore, the concept of divine stewardship emerges as an interfaith convergence point with integrative potential for fostering ecological cooperation. These findings affirm that eco-theology is not only theologically relevant but also strategically significant in driving sustainable interfaith value transformation and collaborative action in the face of the global ecological crisis.